Children’s feelings and attitudes regarding elder abuse - Luchesi, Bruna Moretti (2013)
ABSTRACT The objective of this study was to understand children’s feelings and attitudes regarding elder abuse. This qualitative study was performed with 52 children of ages between seven and ten years, who were interviewed using open questions. The answers were recorded, transcribed and submitted to thematic content analysis. Two large themes were identified: The children’s reaction in face of elder abuse, a theme in which the most stated category was “doing something to help”, followed by “not knowing what to do due to the fear of punishment” and “reacting the same way against the assailant”; The children’s feelings in face of elder abuse, which comprised the categories “becoming sad/upset”, “recognizing the elder as frail” and “not being able to identify the feeling”. By exploring children’s perceptions regarding themes with social relevance, such as elder abuse, permits healthcare professionals to develop strategies to inform and support them regarding the issue. Descriptors: Elder Abuse; Child; Nursing.